2021
DOI: 10.1002/cl2.1154
|View full text |Cite|
|
Sign up to set email alerts
|

A comprehensive review of prioritised interventions to improve the health and wellbeing of persons with lived experience of homelessness

Abstract: Background: Homelessness has emerged as a public health priority, with growing numbers of vulnerable populations despite advances in social welfare. In February 2020, the United Nations passed a historic resolution, identifying the need to adopt social-protection systems and ensure access to safe and affordable housing for all.The establishment of housing stability is a critical outcome that intersects with other social inequities. Prior research has shown that in comparison to the general population, people e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 406 publications
(1,792 reference statements)
1
11
0
Order By: Relevance
“…Assertive community treatment approaches are characterised by multi‐disciplinary working and low caseloads offering community‐based, intensive support (Coldwell & Bender, 2007 ). Evidence has supported this approach for homeless individuals because of improved housing stability, mental health and psychiatric outcomes (Moledina et al., 2021 ). Advances in nurse‐led homeless healthcare must therefore adopt structures that support professionals with diverse roles and responsibilities, and facilitate intensive and multi‐agency support to clients (Parsell et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Assertive community treatment approaches are characterised by multi‐disciplinary working and low caseloads offering community‐based, intensive support (Coldwell & Bender, 2007 ). Evidence has supported this approach for homeless individuals because of improved housing stability, mental health and psychiatric outcomes (Moledina et al., 2021 ). Advances in nurse‐led homeless healthcare must therefore adopt structures that support professionals with diverse roles and responsibilities, and facilitate intensive and multi‐agency support to clients (Parsell et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The second relevant review is that by Aliza Moledina and colleagues, published in June 2021 (Moledina et al, 2021). This…”
Section: Previous Reviewsmentioning
confidence: 99%
“…The second relevant review is that by Aliza Moledina and colleagues, published in June 2021 (Moledina et al, 2021). This review examined a range of different interventions aimed at people experiencing homelessness, including housing, income assistance, case management, mental ill health, and problematic substance use interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Permanent supportive housing interventions, such as Housing First, provide rapid access to non‐abstinence‐based housing and coordinated case management, health, mental health and other support services [ 6 , 7 ]. Two recent meta‐analyses found that permanent supportive housing increases housing stability but has no measurable effect on psychiatric symptom severity or substance use compared with usual services [ 6 , 8 ]. These studies informed the development of a Canadian clinical guideline for people who are vulnerably housed or with experience of homelessness aimed at preventing homelessness and improving health, mental health and social outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specialist homelessness services typically provide case managed support, crisis and transitional accommodation, time‐limited supportive housing and advocacy to enter housing [ 21 ]. In standard case management, the average worker‐to‐client ratio is 1:35 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%